Special aspects of steroid hormone receptors’ expression in cases of cervical intraepithelial neoplasia depending on the papillomavirus infection progression in women with infertility - Kindrativ, E. O.; Chuiko, N. Y.; Zhurakivska, O. Y. (Regulatory Mechanisms in Biosystems, 2020)
The relevance of the study is contingent on insufficient study of the correlation between the reception of uterine cervix steroid hormones in cases of cervical intraepithelial neoplasia (CIN) and the level of human papilloma virus load in women with infertility. The goal of the research was to determine the peculiar features of cervix estrogen and progesterone receptors’ expression at different severity levels of cervical dysplasia, depending on the progression of Papilloma Viral Infection (PVI) in women with infertility. The material for the study was 157 cervical biopsy specimens: 62 – with a mild CIN; 53 – with a moderate CIN; 42 – with a severe CIN. For the immunohistochemical (IHC) test we used primary monoclonal antibodies to estrogen (ER) (clone 6F11, Novocastra) and progesterone receptors (PR) (clone 1A6, Novocastra) as well as the latest generation imaging system UltraVision LP (Lab Vision), chromogen (DAB (Lab Vision)). With PVI-associated CIN with infertility a redistribution of steroid receptor expression was determined; thus, estrogen receptors are characterised by reduction of epithelial and appearance of stromal reaction. But the progesterone receptors’ expression differs by appearance of positive epithelial expression with manifested reaction in the cervical stroma. Redistribution of steroid hormone reception under CIN is predominantly observed in women with tubal infertility. There was a significant decrease in the ER/PR index, with the lowest indicator in the group of patients with severe CIN. Negative expression of steroid hormone receptors is typical for high viral load, regardless of CIN severity level. Thus, in women with infertility, estrogen and progesterone receptors’ expression depends on CIN severity level and PVI progression level. Determining steroid hormone receptors’ expression under PVI-associated CIN in women with infertility may be used as an additional criterion for CIN severity level determination.